Association between tumour infiltrating lymphocytes, histotype and clinical outcome in epithelial ovarian cancer - James, Fiona R.; Jiminez-Linan, Mercedes; Alsop, Jennifer; Mack, Marie; Song, Honglin; Brenton, James D.; Pharoah, Paul D. P.; Ali, H. Raza (BMC cancer, 2017)
Background There is evidence that some ovarian tumours evoke an immune response, which can be assessed by tumour infiltrating lymphocytes (TILs). To facilitate adoption of TILs as a clinical biomarker, a standardised method for their H&E visual evaluation has been validated in breast cancer. Methods We sought to investigate the prognostic significance of TILs in a study of 953 invasive epithelial ovarian cancer tumour samples, both primary and metastatic, from 707 patients from the prospective population-based SEARCH study. TILs were analysed using a standardised method based on H&E staining producing a percentage score for stromal and intratumoral compartments. We used Cox regression to estimate hazard ratios of the association between TILs and survival. Results The extent of stromal and intra-tumoral TILs were correlated in the primary tumours ( n = 679, Spearman’s rank correlation = 0.60, P < 0.001) with a similar correlation in secondary tumours ( n = 224, Spearman’s rank correlation = 0.62, P < 0.001). There was a weak correlation between stromal TIL levels in primary and secondary tumour samples (Spearman’s rank correlation = 0.29, P < 0.001) and intra-tumoral TIL levels in primary and secondary tumour samples (Spearman’s rank correlation = 0.19, P = 0.0094). The extent of stromal TILs differed between histotypes (Pearson chi2 (12d.f.) 54.1, P < 0.0001) with higher levels of stromal infiltration in the high-grade serous and endometriod cases. A significant association was observed for higher intratumoral TIL levels and a favourable prognosis (HR 0.74 95% CI 0.55–1.00 p = 0.047). Conclusion This study is the largest collection of epithelial ovarian tumour samples evaluated for TILs. We have shown that stromal and intratumoral TIL levels are correlated and that their levels correlate with clinical variables such as tumour histological subtype. We have also shown that increased levels of both intratumoral and stromal TILs are associated with a better prognosis; however, this is only statistically significant for intratumoral TILs. This study suggests that a clinically useful immune prognostic indicator in epithelial ovarian cancer could be developed using this technique.